Integrated approaches to sustainable urban development: the synergy between landscape architecture and civil engineering - Sulaksha Wimalasena; Thilina Ganganath Weerakoon; Jayathma Wimalasena (Mokslas: Lietuvos Ateitis)
This research study addresses the developing synergy between landscape architecture and civil engineering in the context of sustainable urban development. The study intends to analyze how these multidisciplinary professions might collectively handle urban difficulties while assuring long-term environmental, social, and economic sustainability. Using the PRISMA technique, the study thoroughly reviewed secondary data from the Scopus database, identifying 23 relevant publications published between 2015 and 2024. The study outlines major integration techniques, obstacles, and emerging trends that impact the cooperation between various disciplines. The results emphasize major impediments to successful multidisciplinary collaboration, including policy fragmentation, inadequate cross-disciplinary education, and technology adaption issues. Additionally, the research underlines the significance of merging theoretical frameworks and practical case studies to increase the knowledge of integrated urban development techniques. By offering a comprehensive examination of the literature, this study adds to a greater knowledge of interdisciplinary urban planning solutions and gives significant insights for policymakers, academics, and practitioners working toward resilient and adaptable urban environments.